(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This study explores the spiritual therapeutic dimensions of Surah al-Fātiḥah through the lens of i‘jāz qur’ānī (Qur’anic inimitability). Al-Fātiḥah, known as Umm al-Kitāb and al-Sab‘ al-Mathānī, functions not only as the essential supplication in worship but also as a profound source of spiritual healing. By examining classical and contemporary tafsīr, this research reveals that al-Fātiḥah contains a healing power (syifā’) believed to bring inner peace, enhance spiritual quality, and serve as a remedy for spiritual ailments. The research applies a qualitative library-based method using thematic exegesis (tafsīr maudhū‘ī) and analysis of i‘jāz qur’ānī. The findings indicate that the spiritual therapy in al-Fātiḥah represents a manifestation of the Qur’an’s miraculous nature, evident in its linguistic beauty, supplicatory structure, and psychological-spiritual impact on its readers and practitioners.